Application of the Science Process Skill Approach in Improving Student Activities and Learning Outcomes in Science Subjects in Kabuyu Inpres Elementary School - Catri, Ni Made; Tangge, Lilies N.; Afadil, Afadil (Jurnal Riset Pendidikan MIPA, 2019)
This study aims to describe the increase in activities and student learning outcomes in learning Natural Sciences in class V Kabuyu Inpres Elementary School through the application of the science process skills approach. The method used in this research is classroom action research which consists of 4 stages, planning, implementation, observation, and reflection, with data collection techniques using evaluation tests, observation sheets, and field notes. Research subjects were 27 students. The results showed that using existing instructional devices showed an increase in student and teacher activities. Student learning activity shows the percentage score obtained on the first cycle is 70.05% in the category enough, in the second cycle showed an increase in the percentage score of 90.48% category very good, an increase of 20.43%. Teacher observation activities when applying the material in class I showed a percentage score of 78.33% in the good category, in the second cycle, the percentage score was 95.00% in the very good category, an increase of 16.67%. In the results of the analysis of evaluation tests, the first cycle students showed the percentage of classical completeness 53.70% for the percentage of classical absorption 71.06%, the second cycle showed an increase in the results of the evaluation test evaluation on the percentage of climax completeness obtained 90.74%, and the percentage of absorption laxative results showed 84.96%, KBK increased by 37.04% and DSK increased by 13.90%. Based on the acquisition of these results, it was concluded that the approach to science process skills can improve student learning activities and outcomes in the heat transfer material in class V of Kabuyu Inpres Elementary School in 2018-2019.